Problems of Tolerance in Students; an Alternative Through the Teachings of Qadiriyah wa Naqsabandiyah Order - Sahri, Sahri; Widiatmaka, Pipit (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
The purpose of this study is to provide an alternative solution for increasing tolerance among Muslim students through the teachings of the Qadiriyah Wa Naqsabandiyah order in the post-conflict region in Indonesia. This research was conducted in West Kalimantan, Indonesia, with data sources from Muslim students at IAIN Pontianak and a total of 15 informants. This research method uses a qualitative research design; data is obtained through observation, interviews, and documentation. Data analysis is carried out through data reduction, data display, verification, and conclusion. The findings in this study revealed that tolerance attitudes in students are still pretense and do not lead to positive tolerance. Therefore, the author provides alternative solutions for building tolerance in students through the teachings of the Qadiriyah Wa Naqsabandiyah Order.